s-Triazolo[3,4-b][1,3,4]thiadiazoles, s-Triazolo[3,4-b][1,3,4]thiadiazines and s-Triazolo[3',4':2,3]thiadiazino[5,6-b]quinoxaline Derivatives of Clubbed Triazole: Novel Pharmacophore as Dual Inhibitors - Ramakrishna, M.; Himabindu, V.; Reddy, T.M.; Chakravarthy, A.K. (Asian Journal of Chemistry, 2011)
N-[5-(4-Amino-5-mercapto-4H-[1,2,4]triazol-3-yl)-4-methyl-1,3-thiazol-2-yl]-acetamide (1) on condensation with chloroacetic acid, a-haloketone and benzoin furnished [1,2,4]triazolo[3,4-b][1,3,4]thiadiazine derivatives (2), (3) and (4), respectively, while condensation with 2,3-dichloroquinoxaline, carbon disulphide, aromatic carboxylic acid and aromatic carboxaldehydes yielded the cyclic products, [1,2,4]triazolo[3,4-b][1,3,4]thiadiazole derivatives (5), (6), (7), (8), respectively. The compounds have been characterized on the basis of elemental analysis and spectral data. The antibacterial and antiinflammatory activities of the compounds have been evaluated. Most of the compounds showed promising activities.